Vocabulary Abilities and Parents’ Emotional Regulation Predict Emotional Regulation in School-Age Children but Not Adolescents With and Without Developmental Language Disorder - Aguilera, Mari; Ahufinger, Nadia; Esteve-Gibert, Núria; Ferinu, Laura; Andreu, Llorenç; Sanz-Torrent, Mònica (Frontiers in Psychology, 2021)
A comprehensive approach, including social and emotional affectations, has been recently proposed as an important framework to understand Developmental Language Disorder (DLD). There is an increasing considerable interest in knowing how language and emotion are related, and as far as we know, the role of the emotional regulation (ER) of parents of children with and without DLD, and their impact on their children’s ER is still unknown. The main aims of this study are to advance our knowledge of ER in school-age children and adolescents with and without DLD, to analyze the predictive value of expressive and receptive vocabulary on ER in school-age children and adolescents, and to explore parental ER and their effect on their children’s and adolescents’ ER. To cover all objectives, we carried out three studies. In the first and second study, expressive and receptive vocabulary were assessed in wave 1, and ER (Emotional Regulation Checklist -ERC- for children and Emotion Regulation Scale -DERS- for adolescents) was assessed in wave 2, four years later. Participants in the first study consisted of two groups of school-aged children (13 had DLD and 20 were typically developing children -TD). Participants in the second study consisted of two groups of adolescents (16 had DLD and 16 were TD adolescents). In the third study, the ER of 65 of the parents of the children and adolescents from study 1 were assessed during wave 2 via self-reporting the DERS questionnaire. Results showed no significant differences in ER between DLD and TD groups neither in middle childhood nor in adolescence. Concerning vocabulary and ER, expressive language predicted ER in school-age children but not in adolescents. Finally, parental ER explained their school-age children’s ER, but this was not the case in adolescents. In conclusion, the present data indicated that expressive vocabulary has a fundamental role in ER, at least during primary school years, and adds new evidence of the impact of parents’ ER upon their children’s ER, encouraging educators and speech language pathologists to include parents’ assessments in holistic evaluations and interventions for children with language and ER difficulties.